An In-Depth Study of Assesing the Factors Affecting Higher education in South-East Asia: A Case Study of Two Universities - Wong, Edward Sek Khin; Heng, Teoh Ngee (The South East Asian Journal of Management, 2009)
The purpose of this study is to determine whether or not selected factors are related to faculty job satisfaction and dissatisfaction at two selected private unversities in South-East Asia. It is an attempt to find out how faculty members feel about their jobs. What pleases them in their work? What are the intrinsic rewards they attain? What brings dissatisfaction or tends to frustrate them? Hence, this study employs the Herzberg Two-Factor theory to determine how selected factors are related to job satisfaction of university faculty members. The conclusions drawn from this study are that the major sources of job satisfaction for university faculty members are shown to be policy and administration, and salary. The relevant sources of dissatisfaction were personal achievement, personal growth, interpersonal relations, recognition, responsibility, supervision, the work itself, and the overall working conditions. The study also has a number of practical impliations for institutional administrators, because if the educational intitution has no instrument designed to measure faculty perceptions of their jobs and work, these administrators could elect to use the same instrument that investigates the areas of job satisfaction to gain similar results.